2011
DOI: 10.1097/pec.0b013e318226c79a
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Pediatric Cardiorespiratory Arrest in Galicia

Abstract: In cases of pediatric out-of-hospital CRA in a community with scattered population, after the introduction of the 2005 international CPR recommendations, there was an increase in bystander CPR and changes in immediate treatment were detected. However, these changes did not result in a significant outcome improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our study showed that bystander CPR rates have increased over time, but survival remained unchanged, which was consistent with Fonte et al This result may be related to the types of bystander CPR provided, that is, whether bystander perform chest compression‐only CPR or conventional CPR (chest compressions and rescue breaths). Bystander CPR prompted by ambulance call‐takers is usually chest‐compressions only in WA, although we were not able to determine from our database the type or quality of bystander CPR performed.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that bystander CPR rates have increased over time, but survival remained unchanged, which was consistent with Fonte et al This result may be related to the types of bystander CPR provided, that is, whether bystander perform chest compression‐only CPR or conventional CPR (chest compressions and rescue breaths). Bystander CPR prompted by ambulance call‐takers is usually chest‐compressions only in WA, although we were not able to determine from our database the type or quality of bystander CPR performed.…”
Section: Discussionsupporting
confidence: 91%
“…A subanalysis from this study published in 2005 found that initial survival was 47% and 1-year survival was 26.4% and that patients who were initially resuscitated by laypersons or paramedics had higher survival (53% versus 15.2%; P = 0.001). 4,79…”
Section: Discussionmentioning
confidence: 99%